The Analysis of Factors Influencing Decisions When Buying Laptop - Josua Ferdinand Sedua; Indrajit Indrajit; Ika Prayanthi (CogITo Smart Journal, 2022)
This study aims to find out what factors influence students’ interest in buying laptops. This study used a combination of qualitative and quantitative methods and statistical exploratory factor analysis techniques. The qualitative methods were used in identifying the variables studied, while quantitative methods were used in grouping or categorizing these variables into certain factors. This study used 22 variables that were developed from the results of interviews and filling out questionnaires by 200 student respondents. The results of the study found that there were 5 factors that had the greatest contribution in influencing students to buy laptops. These factors were functional factors, social factors, conditional factors, emotional factors, and hobby factors. The factor that had the greatest influence was the functional factor and the smallest was the hobby factor. Furthermore, based on the results of the independent sample t-test, it was found that there was no significant difference between men and women when viewed from the factors that influenced their interest in buying a laptop.